Coagulation on Endothelial Cells: The Underexposed Part of Virchow’s Triad - Geenen, Irma L.A.; Post, Mark J.; Molin, Daniel G.M.; Schurink, Geert W.H.; Maessen, Jos G.; Oerle, Rene v.; Cate, Hugo ten; Spronk, Henri M.H. (Thrombosis and Haemostasis, 2012)
The process of thrombin generation involves numerous plasma proteases and cofactors. Interaction with the vessel wall, in particular endothelial cells (ECs), influences this process but data on this interaction is limited. We evaluated thrombin generation on EA.hy926, human coronary arterial ECs (HCAECs) and patient-derived human venous ECs (HVECs) by means of a modified calibrated automated thrombogram (CAT) method and especially looked into contribution of the intrinsic and extrinsic pathways. Thrombin generation was measured in presence of confluent ECs with normal pooled and factor XII-deficient (FXII-deficient) platelet-poor plasma, with/without active site inhibited factor VIIa (ASIS) to block the extrinsic pathway and corn trypsin inhibitor for blocking contact activation (intrinsic pathway). Fetal bovine serum (FBS) was removed from culture conditions as FXIIa from the serum retained on ECs apparently, thereby inducing strong contact activation. In serum-free conditions, EA.hy926 and patient-derived HVECs induced thrombin generation mainly via the contact activation pathway with minor influence of ASIS on peak height and very low thrombin generation curves in FXII-deficient plasma. HVECs derived from coronary arterial bypass graft (CABG) patients showed increased thrombin generation compared to control patients, which could be ascribed to increased contact activation. Contribution of the extrinsic pathway on patient-derived ECs was limited. We conclude that the CAT method in combination with serum-free cultured ECs offers a valuable high-throughput method to evaluate endothelial influences on thrombin generation, which appears to involve predominantly contact activation on ECs. Contact activation-mediated thrombin generation was increased on ECs from CABG patients compared to controls.
Keywords: Endothelial cells; thrombin generation; cell culture; contact activation; extrinsic pathway